Comparison of Recurrence Rates in Patients with Locally Advanced Breast Cancer after Mastectomy and Received Aromatase Inhibitor Therapy with Steroids and Nonsteroids - I Ketut Yante; Desak Gede Agung Suprabawati; Iskandar Ali (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2021)
Introduction. Breast cancer is a problem that is still faced throughout the world. The incidence of cancer in Indonesia is at number 8 in Southeast Asia. The incidence of breast cancer in women is 42.1 per 100,000 population. Aromatase inhibitors are hormonal therapy used in postmenopausal breast cancer with positive ER and/or positive PR. The third generation aromatase inhibitors are divided into 2 categories, namely non-steroidal agents that are reversible and steroid agents that are irreversible. Based on existing studies, there are no consistent research results regarding the incidence of recurrence after aromatase inhibitor therapy, both steroids and non-steroidal. Methods. This study is an analytical observational study with a retrospective cross-sectional design using secondary data from medical records. The research was carried out at the Surgical Clinic of RSUD dr. Soetomo Surabaya on October 1, 2020 until the end with the subject of LABC patients at POSA Surgery RSUD Dr. Soetomo who has undergone mastectomy and radiotherapy and has received adjuvant hormonal aromatase inhibitor therapy for 2 years from January 2018 to January 2020. Results. In the nonsteroidal aromatase inhibitor group, 18 subjects (60%) experienced recurrence and 16 subjects in the steroid aromatase inhibitor group (32%) with an OR of 0.314 (0.12-0.81; p=0.014. Based on the results of multivariate analysis, it was found that the increased risk of recurrence was significantly affected only by the administration of aromatase inhibitor p= 0.052 Conclusion. Women with locally advanced breast cancer after mastectomy who received aromatase inhibitor steroid therapy had a 0.314 times lower risk of recurrence than those who received non-steroidal aromatase inhibitor therapy.